Pengaruh Tingkat Ketergantungan, Opini Audit, Ukuran Legislatif dan Rasio Kemandirian Terhadap Pengungkapan Laporan Keuangan Pemerintah Provinsi di Indonesia - Gea Ananda; Yevi Dwitayanti; Sarikadarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to determine how the disclosure of provincial government financial reports in Indonesia is influenced by the level of dependence, audit opinion, legislative size, and independence ratio. This study uses secondary data and a quantitative approach. This study was conducted in all 34 provinces in Indonesia for the period 2021-2023 with a sample size of 102. Financial reports in the form of Audit Result Reports (LHP) are used as a data source for this study which are obtained through the official website of the BPK RI through the pages www.bpk.go.id and www.puskapol.fisip.ui.ac.id to obtain the source of the number of members of the Regional People's Representative Council (DPRD). The sample selection technique in the study used an approach using purposive sampling. The data analyzed using SPSS software version 26. The results of this study individually Dependence Level, Audit Opinion and Legislative Size have an effect on the Disclosure of Provincial Government Financial Reports in Indonesia. Meanwhile, the Independence Ratio does not show any effect on the Disclosure of Provincial Government Financial Reports in Indonesia.